Risk of groundwater pollution in open dug wells in the Pungudutivu Island of the Jaffna Peninsula, Sri Lanka - Pathmaja, S.; Dharmagunawardhane, H.A.; Senthilnanthanan, M.; Mikunthan, T.; Rajasooriyar, L.D. (Geological society of Sri lanka, 2019)
Un-protected open dug wells of shallow groundwater environments are subjected to high risk of chemical and microbial pollution in many parts of the world. The present study was initiated in Pungudutivu, one of the surrounding islands of the Jaffna Peninsula, Sri Lanka, because the island totally relies on its limited groundwater resources extracted from open dug wells to meet all its needs. The study assessed the risk of pollution within the limited fresh groundwater found in unconfined aquifer systems of Pungudutivu, where high risk of pollution was expected mainly from organic sources, derived from human and animal wastes and easy infiltration and runoff returns. The fresh groundwater pockets of Pungudutivu were however found to be with less serious contamination risks other than high Fe2+ and high faecal coliform counts. Low nitrate and phosphate concentrations with high COD and low BOD demonstrated less pollution from biodegradable organic sources in the midst of high oxidising potentials in the shallow dug wells as implied by the stability field of Fe(OH)3 on the Eh-pH diagram; the argument of high Fe2+ in groundwater however, wasn't supported by the said oxidation potential. High faecal coliform counts with high DO in groundwater probably indicated conditions implied by on site waste disposal in groundwater of Pungudutivu.
Keywords: Ground water; Pollution; Risk; Pungudutivu; Jaffna Peninsula